2012
DOI: 10.1155/2012/902413
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electroacupuncture at Head Points on the Function of Cerebral Motor Areas in Stroke Patients: A PET Study

Abstract: Positron emission tomography (PET) is used to observe the cerebral function widely and is a good method to explore the mechanism of acupuncture treatment on the central nervous system. By using this method, we observed the cerebral function of 6 patients suffering from ischemic stroke after receiving EA treatment at Baihui(GV20) and right Qubin(GB7). The results were: (1) the glucose metabolism changed significantly on primary motor area (M1), premotor cortex (PMC), and superior parietal louble (LPs) bilateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 24 publications
1
34
0
Order By: Relevance
“…Numerous studies have attempted to elucidate the pathophysiological mechanisms of acupuncture effects on various chronic pain symptoms in both patients and experimental animal models [9–11]. In order to identify the effects of acupuncture treatment, previous studies observed changes in blood pressure, activity changes of endogenous opioids within the central nervous system (CNS) [12], and brain activation by, using advanced technologies such as electroencephalogram [13], functional magnetic resonance imaging (fMRI) [14], and positron emission tomography [15]. Despite these efforts, the mechanisms of acupuncture-induced analgesia remain unclear [11, 16].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have attempted to elucidate the pathophysiological mechanisms of acupuncture effects on various chronic pain symptoms in both patients and experimental animal models [9–11]. In order to identify the effects of acupuncture treatment, previous studies observed changes in blood pressure, activity changes of endogenous opioids within the central nervous system (CNS) [12], and brain activation by, using advanced technologies such as electroencephalogram [13], functional magnetic resonance imaging (fMRI) [14], and positron emission tomography [15]. Despite these efforts, the mechanisms of acupuncture-induced analgesia remain unclear [11, 16].…”
Section: Introductionmentioning
confidence: 99%
“…Among different acupoints, Baihui (GV20) and Dazhui (GV14) are the main points of the Du channel, which exhibits a combined supervising effect on the entire meridian system. Acupuncture at Baihui in combination with Dazhui promoted flow of blood, resuscitated consciousness, recuperated depleted yang, and balanced Yin and Yang (Fang et al, 2012). Amounting evidence of animal experiments have shown that acupuncture at the points located in the head and the neck could improve the blood circulation system of the brain, dilate brain blood vessel, improve the microcirculation, ameliorate cerebral edema, and activate the repair function of cerebral neurons to promote functional recovery (Kim et al, 2011;Chuang et al, 2007;Liu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It has been frequently used in Asian countries and has become increasingly popular in the western world (MacPherson and Hammerschlag, 2012;Fang et al, 2012;Ji and Zhang, 2009;Zhou et al, 2009). …”
mentioning
confidence: 99%
“…Besides these areas related to motion directly, glucose metabolism had also changed in the middle and superior temporal gyrus, putamen and cerebellum. These findings suggested that the contralateral hemisphere played an important role in the stroke recovery process (Pantano et al, 1996) and that EA treatment for stroke patients had played a good role in the recovery of motor function, since it proved very helpful for the cerebral motor plasticity after ischemic stroke (Fang et al, 2012).…”
Section: Clinical Studiesmentioning
confidence: 94%
“…In a PET study of 6 patients after ischemic stroke, 2 Hz EA treatment at Baihui (GV20) and right Qubin (GB7, on the affected hemisphere) for 20 min resulted in a significant increase of glucose metabolism on the primary motor area (M1), the precentral gyrus, the supplementary motor area (SMA), the medial frontal gyrus, premotor cortex (PMC), the central frontal gyrus and the superior parietal lobule (Lps) of the unaffected side, while in the affected side glucose metabolism was decreased on M1, PMC and Lps (Fang et al, 2012). Besides these areas related to motion directly, glucose metabolism had also changed in the middle and superior temporal gyrus, putamen and cerebellum.…”
Section: Clinical Studiesmentioning
confidence: 99%